Applying the Scrum Method in Software Development for Undergraduate Thesis Project Implementation - Attaf Riski Putra Ramadhan; Indra Waspada; Nurdin Bahtiar; Adhe Setya Pramayoga (Jurnal Masyarakat Informatika, 2025)
The Scrum Method, as one of the frameworks within Agile-based software development, has become the de facto standard in industry practices. However, to date, there is no specific guideline or adaptation model that directs the application of Scrum in undergraduate thesis project settings, particularly within the Bachelor of Informatics Study Program at Diponegoro University. In this program, the final project is carried out individually by a student under the supervision of two academic advisors, forming a small team structure that differs from conventional Scrum configurations. This study proposes an adaptation model of the Scrum method for such a scenario, assigning the roles of Product Owner and Tester to the First Supervisor, Scrum Master and Tester to the Second Supervisor, and Developer as well as Assistant to the Student. The implementation of Scrum in this context facilitates structured communication between supervisors and the student, while also supporting flexibility in accommodating changing requirements throughout the development process. Moreover, active stakeholder involvement during the requirements gathering and Sprint Review stages contributes to the enhanced quality of the final deliverable. The project was executed over four sprints within a total of 40 working days, covering 13 product backlog and several derivative tasks. The findings indicate that adapting Scrum to the context of a final project enables timely project completion with outcomes that are academically and technically accountable.